A descriptive study on the career choices made by UPCD Graduates from Batch 1995 - 2005 residing in the Philippines - Marabe, Layra I.; Modina, Jennifer Fairuz C.; Yumul, Giselle C. (Adviser).
This study was done among graduates of the University of the Philippines, College of Dentistry (UPCD) from batch 1995 to 2005 that are working and residing here in the country. This was carried out primarily to determine the current trend in the career options made by UPCD graduates and the reasons behind such choices. Three hundred seventy-two (372) graduates were included in the study. The survey questionnaires were sent through mail with an attached self-addressed stamped envelope (SASE) and also through a website (www.FreeOnlineSurvey.com). Of the total population, 58 respondents have participated. 44 of the subjects have responded through regular mail while 14 answered through the online survey on the website. Results showed that 66.7% of the UPCD participating graduates of Batch 1995 - 2005 choose associateship as the immediate type of private practice and 71.4% choose teaching as non-private practice. But it was also observed that career choices change during the course of their dental practice. And the prevailing shift is towards solo private practice focused on general dentistry. When the entire population was categorized among females, among married respondents and those aged 29 to 36, solo practice is the prevailing type of private practice while among males, among single respondents and those aged 23 to 28. associateship is the choice. Teaching and general practice is common regardless of gender, civil status and age. The respondents who practices for 4 to 11 years with specialization and practices in Metro Manila usually earn more than Php30,000 a month.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dentists--Philippines.; Filipino dentists